2017
DOI: 10.1371/journal.pone.0176149
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and relative bioavailability of an oral amoxicillin-apramycin combination in pigs

Abstract: A new compound granular premix of amoxicillin (20% w/w dry mass)/apramycin (5% w/w dry mass) was developed, and its pharmacokinetics and relative bioavailability were determined in pigs following oral administration following a cross-over study design. The pharmacokinetic parameters of amoxicillin (t1/2λ = 6.43 ± 4.85h, Cmax = 3.2 ± 1.35 μg·mL-1, Tmax = 1.92 ± 0.58, AUCINF = 8.98 ± 2.11 h·μg·mL-1) and apramycin (t1/2λ = 8.67±4.4h, Cmax = 0.23 ± 0.12 μg·mL-1, Tmax = 2.25 ± 0.82 h, AUCINF = 12.37 ± 8.64h·μg·mL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…PK studies on APR were mainly based on PK data in plasma. Previous result showed that the peak plasma concentration of APR was 0.23 µg/mL and reached at 2.25 h, the AUC INF was 1.59 h•µg/mL in plasma after oral administration of 4 mg/kg [24]. The corresponding PK parameters of the C max and AUC INF were lower observed in plasma of pigs and in broiler chickens [25,26].…”
Section: Discussionmentioning
confidence: 91%
“…PK studies on APR were mainly based on PK data in plasma. Previous result showed that the peak plasma concentration of APR was 0.23 µg/mL and reached at 2.25 h, the AUC INF was 1.59 h•µg/mL in plasma after oral administration of 4 mg/kg [24]. The corresponding PK parameters of the C max and AUC INF were lower observed in plasma of pigs and in broiler chickens [25,26].…”
Section: Discussionmentioning
confidence: 91%
“…It was not possible to study the consumption of the medicated feed by the (individual) pigs in the current study. However, other studies [9,10,15] show a large variability in feed consumption between pigs housed in the same pen and stable. Given this large variability, the risk is estimated to be 'moderate to high' based on available literature.…”
Section: • Module 4: Consumption Of Medicated Feed By the Pigsmentioning
confidence: 95%
“…For antimicrobial treatment to be efficacious, several parameters play a crucial role: the choice of the medicine, the homogeneity and stability of the drug in feed or water [6,7], the dose ingested by the individual animal, and drug factors that affect whether or not the pharmacokinetic/pharmacodynamic (PK/PD) breakpoint is reached [8]. Noticeably, high variability in plasma concentrations is observed in individual pigs after the provision of medicated feed [9,10] and drinking water [11][12][13][14]. Several reasons can account for this variability, namely different intake due to social hierarchy and (sub)clinical illness, homogeneity, stability as well as palatability [2,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioavailability of apramycin is very low; about 4% in pigs (Dai et al., 2017 ) and 2% in broilers (Afifi and Ramadan, 1997 ). Very low serum concentrations were also described after oral administration to calves (Ziv et al., 1985 ).…”
Section: Introductionmentioning
confidence: 99%